(untitled) (Clinics, 2019)
OBJECTIVE: To assess work ability and productivity in patients with diabetic foot. METHODS: This investigation was a cross-sectional controlled study. A total of 117 individuals were selected from March to June 2014 and allocated to group A (patients without diabetes, n=43), group B (diabetes patients without foot ulcers, n=43), or group C (patients with diabetic foot, n=31). Two validated instruments, the Work Limitations Questionnaire (WLQ) and the Work Productivity and Activity Impairment Questionnaire General Health v2.0 (WPAI-GH), were used to assess work ability and productivity. RESULTS: The groups were homogeneous regarding age and sex; however, patients in group C had a lower education level than the other participants (p=0.006). The median WLQ scores for groups A, B, and C were 0.0121, 0.0146, and 0.0852, respectively (po0.0001). The WPAI-GH scores revealed a mean productivity loss of 20% for groups A and B and 100% for group C (po0.0001). CONCLUSIONS: Patients with diabetic foot showed decreased work ability and productivity.